Comparative evaluation of efficiency of burn wound healing with derma-based hydrogel: a preclinical experimental study - K. I. Melkonyan; S. N. Alekseenko; I. M. Bykov (Кубанский научный медицинский вестник, 2023)
Background. Burn wound healing is recognized as a complex process involving synergetic interactions between different cells, cytokines and growth factors. The adverse interactions can underlie chronicization of the process. Accordingly, the paper presents a relevant study into mechanisms of natural wound dressings, capable of influencing the processes of inflammation, angiogenesis, and skin resurfacing.Objective. To carry out a comparative evaluation of efficiency of burn wound healing with derma-based hydrogel according to the dynamics of proand anti-inflammatory factors.Methods. Development of a hydrogel material involved dermis samples of Landrace breed of pig, subjected to partial alkaline hydrolysis. In order to carry out a comparative evaluation of burn wound healing efficiency, the authors simulated direct thermal injury in three groups of sphinx (hairless) rats: group 1 (control group) — rats without treatment (n = 20), group 2 (comparison group) — rats treated with Levomekol ointment (n = 20), and group 3 (experimental group) — rats treated with hydrogel material (n = 20). Before and after injuring on days 1, 3, 7, 14, the content of cytokines interleukin-1β, interleukin-4, interleukin-6, interleukin-8, interleukin-10, tumor necrosis factor-α by enzyme immunoassay. The wound samples were explanted for histological examination on days 3, 7 and 14 after the beginning of the experiment. Statistical processing of the obtained results on DNA content in hydrogel, cytokine content in serum and morphometric data was performed using GraphPadPrism 6.04, Microsoft Excel 2016 (Microsoft, USA).Results. When determining the content dynamics of nonspecific markers of inflammation, an increase in the concentrations of interleukin-1β and tumor necrosis factor-α on day 1 after the hydrogel application was recorded, as well as an increase in interleukin-6 on days 3 and 7, while the concentrations of interleukin-8 did not change significantly throughout the experiment. Thus, dermal components are indicated to participate in the inhibition of acute-phase immune reactions. With regard to anti-inflammatory factors, the study revealed a decrease in the concentration of interleukin-10 on days 1 and 7, an increase in interleukin-4 on day 3 as compared to the control group, thereby indicating a pronounced anti-inflammatory effect and prolonged action of the hydrogel.Conclusion. Comparative analysis of the pro-inflammatory cytokines levels (interleukin-1β, interleukin-8) showed pronounced anti-inflammatory effects of the derma-based hydrogel material. Introduction of exogenous biological components of the extracellular matrix (collagen and its hydrolysates) had a significant influence on the regulation of anti-inflammatory cytokines synthesis, presumably contributing to faster successful epithelization and wound healing.